2010
DOI: 10.1080/15320383.2011.528471
|View full text |Cite
|
Sign up to set email alerts
|

Chromium and Lead Concentrations in Tomatoes (Solanum Lycopersicum) and Red Peppers (Capsicum Frutescens) Cultivated in Roadside Farmland around High Traffic Density Area of Ibadan, Nigeria

Abstract: The total concentrations of Pb and Cr were determined in tomatoes and peppers cultivated in roadside farmland around a high traffic density area of Ibadan. The measurements were determined by atomic absorption spectrophotometer after wet digestion with nitric acid. The ranges of accumulation factors (AF) for Cr in tomatoes and pepper were 6.25-6.63 and 2. 86-4.86. The degree of accumulation of Pb in tomatoes ranged from 30.5 to 40.6. Tomatoes and peppers planted in farms located near high traffic roads present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Crop production and food safety has been an important issue due to traffic-related contamination along highways where crops are grown. Feng et al (2011) Olayinka and Ipeaiyeda (2011). It was found that Cr and Pb vegetable concentrations found at farms near high traffic density were higher than those found in a control farm.…”
Section: Toxicology and Health Riskmentioning
confidence: 87%
“…Crop production and food safety has been an important issue due to traffic-related contamination along highways where crops are grown. Feng et al (2011) Olayinka and Ipeaiyeda (2011). It was found that Cr and Pb vegetable concentrations found at farms near high traffic density were higher than those found in a control farm.…”
Section: Toxicology and Health Riskmentioning
confidence: 87%
“…Vegetables are essential components of the human diet, but studies have demonstrated the presence of trace metals in them. Vegetables grown under heavily polluted water may have heavy metals contamination [40].…”
Section: Chromium Detection In Real-life Samplesmentioning
confidence: 99%
“…Vegetables grown in heavily polluted water may show heavy-metal contamination. 40 These metals cannot be removed by washing the vegetables or cooking, even at high temperatures. Hence, we have explored the possible detection of Cr 3+ in tomatoes (Solanum lycopersicon) using the probe HJ-DNP.…”
Section: Chromium Detection In Real-life Samplesmentioning
confidence: 99%